2007
DOI: 10.1007/s10792-007-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in optic pit maculopathy

Abstract: These findings support the concept of a bilaminar structure that contains retinoschisis and serous macular detachment. Our data also showed that in some patients, the sole component of maculopathy was serous macular detachment or retinoschisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…The elements of these two components are serous macular detachment and retinoschisis, which are typical for this disease [10,11]. We also observed these two components clearly in all our cases; a similar finding to a study by Karacorlu et al [10].…”
Section: Discussionsupporting
confidence: 92%
“…The elements of these two components are serous macular detachment and retinoschisis, which are typical for this disease [10,11]. We also observed these two components clearly in all our cases; a similar finding to a study by Karacorlu et al [10].…”
Section: Discussionsupporting
confidence: 92%
“…19 Vitrectomy combined with gas tamponade, 10,13 endophotocoagualtion, 11 silicone oil, 20 ILM peeling, 21 or sub-retinal fluid drainage 22 have also been performed with a relatively high success rate. Our results show that vitrectomy is not the only way to relieve vitreous traction, especially in cases where no obvious tractional force was noted on OCT. Vitreous traction was found only in some patients with ODPM, 23 further raising concerns about the use of vitrectomy in all cases of ODP. In our nine eyes, only one patient had vitreomacular traction before treatment (patient 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several OCT studies have demonstrated vitreous strands over ODPs [28, 30, 40]. Several reports describe a membrane over the ODP [4143], and it has been noted that ODP-M can develop after this membrane disappears, presumably due to vitreous traction over it [44, 45]. On the other hand, ODP-M can occur in pediatric patients before the onset of any changes in the vitreous, and also in adults without PVD [1, 13, 19].…”
Section: Reviewmentioning
confidence: 99%